DIATHERMY VERSUS SCALPEL INCISIONS FOR OPEN CHOLECYSTECTOMY —— A COMPARATIVE STUDY: Open Cholecystectomy - Niazi, Waseem Ahmed Khan; Ali, Muhammad Asghar (Pakistan Armed Forces Medical Journal, 2014)
Objective: The aim of the study was to make a comparison between skin incisions made with electrocautery versus scalpel in terms of their safety, efficacy and post-operative complications. Design: A randomized controlled study. Setting: The study was conducted in Combined Military Hospital (CMH) Kharian, Pakistan airforce (PAF) Hospital Sargodha. Duration of Study: May 2008 to August 2011. Patients and Methods: Ninety seven patients who underwent open cholecystectomy were randomly divided into two groups on the basis of the use of electrocautery versus steel scalpel for making skin incision and subcutaneous tissue dissection. Parameters recorded were, time taken from skin incision to full incising of the peritoneum, length of the wound, amount of blood loss during this step of surgery in each group. Post-operative pain scoring using visual analogue scale was done. Wound complications such as infection, haematoma/seroma and dehiscence were noted too. One month of follow up was recorded in each group. Subsequently a comparison of these findings was done. Results: Incision time (sec/cm2) was longer in scalpel group than in diathermy group (p = 0.001), whereas, incision blood loss (ml/cm2) was significantly less in diathermy group than in scalpel group (p = 0.03). There was no difference in post-operative pain perception as delineated by visual pain analogue scoring system between the two groups (p = 0.57). Post-operative wound complications and the final healing of wound at 01month of followup were almost similar in both groups. Conclusion: Electrocautery may be used safely without any untoward complication in making skin incision and sub-cutaneous tissue dissection with an advantage of reduced incision time and and less blood loss.